ANALISIS VOLATILITAS CRYPTOCURRENCY PADA SEBELUM PANDEMI DAN PADA SAAT PANDEMI COVID 19 DENGAN METODE RETURN PADA BITCOIN DAN ETHEREUM - Kuncara, Tommy; Anugrah, Kharisma Putra (KEUNIS, 2023)
Cryptocurrencies like Bitcoin, Ethereum and are high volatility digital commodities, so using them as an alternative to trading investments is very dangerous. Volatility analysis, portfolio formation, and implementation forecasts need to be carried out to minimize risk   levels and risk management to help investors/traders make decisions. If you estimate, its use is suitable for analyzing the returns and volatility of cryptocurrencies. The Metode used in this study are methods of converting data into returns, detecting constancy with the ADF test, and normality testing with the JarqueBera test. The result of this study is that there are differences in the rate of return on bitcoin and ethereum coins every year, in these two crypto coins have experienced a very significant increase from before the covid 19 pandemic to covid 19. The result of this study is that there are differences in the rate of return on bitcoin and ethereum coins every year, in these two crypto coins have experienced a very significant increase from before the covid 19 pandemic to covid 19.